1996
DOI: 10.1074/jbc.271.4.2234
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Functional Domains on the C-terminal Region of Caldesmon Using Full-length and Mutant Caldesmon Molecules

Abstract: A series of C-terminal deletion mutants of chicken gizzard smooth muscle caldesmon (CaD) were made using a polymerase chain reaction cloning strategy and a baculovirus expression system, and the precise locations of the functional domains of CaD involved in the regulation of actomyosin ATPase and the binding of actin, tropomyosin, and calmodulin were analyzed. Our results reveal a high affinity calmodulin-binding domain that consists of at least three calmodulin-binding determinants localized in residues 690 -… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
58
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(66 citation statements)
references
References 48 publications
(46 reference statements)
8
58
0
Order By: Relevance
“…Site B′, in contrast, may act as a secondary site whose binding is easily reversible depending on the environment surrounding the thin filament. The weak interaction between site B′ and calmodulin may also explain why some have observed an interaction between calmodulin and caldesmon fragments containing site B′ (Huber et al, 1996;Marston et al, 1994), while others (Wang et al, 1996) did not detect significant changes in binding when the region containing site B′ (residues 718-756) was truncated from caldesmon.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Site B′, in contrast, may act as a secondary site whose binding is easily reversible depending on the environment surrounding the thin filament. The weak interaction between site B′ and calmodulin may also explain why some have observed an interaction between calmodulin and caldesmon fragments containing site B′ (Huber et al, 1996;Marston et al, 1994), while others (Wang et al, 1996) did not detect significant changes in binding when the region containing site B′ (residues 718-756) was truncated from caldesmon.…”
Section: Discussionmentioning
confidence: 99%
“…Recent NMR data by Huber et al (1996) showed the distinct Ca 2+ -calmodulin interaction with Trp residues 692 and 722 at sites B and B′, respectively. Another report by Wang et al (1996) has shown that there are three calmodulin-binding determinants localized within residues 628-717, which encompasses only sites A and B. However, deletion of residues 718-756, containing site B′, had no effect on calmodulin binding.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…65 Subsequently, it was determined that the Tm-binding sites were localized in the C-terminal region. [66][67][68][69][70] This region of the last ~300 amino acid residues not only contains the actin-and the CaM-binding sites, but also harbors TnT-analogous sequences that interact with Tm. 71 Apparently there are several peptide segments in this region that bind actin, Tm and CaM independently (see, for example, 72).…”
Section: Direct Interaction Between Cad and Tmmentioning
confidence: 99%
“…83 Indeed, structural studies showed the C-terminal region of CaD contains multiple β-turns, which allows for plenty of flexibility and facilitates docking on actin filaments. 84 Functionally, the C-terminal region of CaD harbors actin-, CaM-and Tm-binding sites, 68,[85][86][87][88][89] whereas the N-terminal domain contains the major myosin-binding sites [90][91][92] and also interacts with CaM and actin. 93,94 The actin-and myosin-binding capacity enables CaD to play a role in bringing the thin filaments close to the thick filaments (see below).…”
Section: Molecular Shape and Domain Structurementioning
confidence: 99%